The Basha's Tools? Imagining Alternative Justice Futures in Egypt - Ghazal, Farah (AUC Knowledge Fountain, 2021)
The dominant approach to addressing violence against women in Egypt today is carceral, or relying on the punitive instruments of the state to achieve justice (most visibly represented by the prison and police). While carceral responses are perhaps unsurprisingly advocated by state feminism, they are also promoted by what would typically be described as anti-state actors. This paradoxical entanglement takes place during what I identify as the 'carceral moment', a period marked by the intensification of political and social repression and during which incarceration appears more readily available as a solution to remedy perceived problems of governance. I argue that, in this moment, carceral sensibilities dominate among anti-state activism, which often criticizes state violations, such as the conditions under which (mostly political) detainees are held, but fails to demonstrate similar opposition to the prison as such. This project is therefore an attempt to understand the history, extent and context of this limitation, which is understood to be an effect of what is globally known as carceral feminism (CF), or law-and-order feminism. I argue that, alongside CF, perpetual states of emergency imposed in Egypt have also had severe repercussions on its current feminist imaginary, resulting in minor concessions granted by the carceral state being perceived as victories and rendering its carcerality secondary. The United States-specific nature of the prison abolitionist feminist tradition – the leading source of opposition to carceral feminism – is also analyzed. Focusing primarily on the lack of space for thought about alternative approaches to justice rather than locating manifestations of CF in Egypt, this thesis makes the case for orienting the contemporary feminist imaginary away from carceral currents and towards alternative approaches to justice.